Hammond Cards, Inc : the creative acquisition - Mulligan, Paul; Ansari, Shahid; Nanni, Alfred J. (London : Institute of Management Accountants, 2008)
This case is designed to show the interconnection between operations, markets, and strategic cost management. Hammond Cards is thinking of acquiring Creative Designs for operational synergies. The two companies have similar manufacturing operations but different distribution channels and customers. Hammond produces simple greeting cards that are sold through mass market retailers such as Wal-Mart. Hammond's business model is low margin high volume. In contrast, Creative Designs specializes in so-called studio cards. These are high-end greeting cards sold individually at retail. The students have to analyze the expected benefits from the merger. The case requires students to evaluate the operations of both firms including cycle time, demand fluctuations, and quality management. The analysis reveals that the merger is a good idea but not for the original motivation for this decision. The case asks students to develop a post merger plan for how to use the joint production capacity and how to exploit the two markets.
Originally published in Mulligan, P., Ansari, S., & Nanni, A. J., Jr., (2008). Hammond Cards, Inc: The creative acquisition. IMA Education Case Journal, 1(1), Article 1.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Hammond Cards; Creative Designs; Managerial accounting